2016
DOI: 10.1007/s11629-015-3600-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation of spring phenology in Tibetan Plateau and its linkage to climate change from 1982 to 2012

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The advancement of SG is about 10.4 days decade −1 from 2001 to 2012 in Tibetan Plateau, based on combined AVHRR NDVI over 1982-2000and SPOT-VGT NDVI over 2001(Zhang et al 2013. However, this magnitude of SG shift is very different from the SG trend over 2000-2011 inferred from single AVHRR NDVI, which inferred insignificant SG trend in the Tibetan Plateau (Ding et al 2016).…”
Section: Introductionmentioning
confidence: 81%
“…The advancement of SG is about 10.4 days decade −1 from 2001 to 2012 in Tibetan Plateau, based on combined AVHRR NDVI over 1982-2000and SPOT-VGT NDVI over 2001(Zhang et al 2013. However, this magnitude of SG shift is very different from the SG trend over 2000-2011 inferred from single AVHRR NDVI, which inferred insignificant SG trend in the Tibetan Plateau (Ding et al 2016).…”
Section: Introductionmentioning
confidence: 81%
“…Yu et al () reported that the SOS of the Tibetan Plateau derived from the GIMMS NDVI data set using the polynomial fitting and NDVI threshold method advanced from 1982 to the mid‐1990s and retreated after the mid‐1990s because of the increasing winter temperature and spring temperature. By contrast, some other studies reported that no significant SOS trend was found from 1982 to 2013 (Ding et al, ; Liu et al, ). Ding et al () used the polynomial method and the GIMMS3g (version 0) and SPOT‐VEG data, while Liu et al () used the logistic method (logistic fitting and NDVI inflection detecting) and the advanced very high resolution radiometer (AVHRR) and MODIS data.…”
Section: Introductionmentioning
confidence: 84%
“…By contrast, some other studies reported that no significant SOS trend was found from 1982 to 2013 (Ding et al, ; Liu et al, ). Ding et al () used the polynomial method and the GIMMS3g (version 0) and SPOT‐VEG data, while Liu et al () used the logistic method (logistic fitting and NDVI inflection detecting) and the advanced very high resolution radiometer (AVHRR) and MODIS data. T. Wang et al () found that the continuously advancing trend in SOS derived from MODIS and SPOT‐VEG NDVI was significantly correlated with the increasing NDVI in January–April induced by the deceasing snow cover fraction.…”
Section: Introductionmentioning
confidence: 84%
“…Lower density of surface observation networks, higher altitudes and complex and diverse natural environments, and vegetation types might be responsible for the inconsistent distributions. Ding et al [2] analyzed the relationship between the start of the growing season and temperature and precipitation over the Tibetan Plateau and found regions with significant delay for the start of the growing season were mostly distributed in the semi-arid areas, while regions with significant advance of the start were mainly scattered in humid and semi-humid areas from 1982 to 2012. In relatively humid area, the start of the growing season was significantly correlated with spring temperature, and the importance of spring temperature gradually decreased with increasing aridity.…”
Section: Discussionmentioning
confidence: 99%
“…3-4.8 ∘ C relative to 1986-2005 [1]. Changes in the vegetation growing season have received much attention as the timing and length of the growing season are sensitive to climate variation and global warming [2,3], and changes in the growing season can also affect the function and service of ecosystems (e.g., agricultural production, carbon sequestration potential, soil and water conservation, and biological diversity) and global and regional climate [4][5][6]. An increasing number of studies, based on climatological, phonological, and satellite remote sensing data, have reported an earlier spring, later autumn, and consequently prolonged growing season over most of the Northern Hemisphere in the twentieth century [1,6], though the earlier onset of the growing season was slowed down in the first decade of the twenty-first century [3].…”
Section: Introductionmentioning
confidence: 99%